Response to Association Between Preinfarction Angina and Angiographic Findings in Non–ST‐Segment Elevation Myocardial Infarction - Bajka, Balazs (Clin Cardiol, 2016)
Misumida N et al. Clin Cardiol. 2015;38:535–541.